2007
DOI: 10.1029/2006ja012169
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic simulations of transient transpolar potential responses to solar wind density changes

Abstract: [1] Magnetohydrodynamic (MHD) simulations are used to examine the response of the transpolar potential (F TP ) to changes in the solar wind density during periods of constant solar wind electric field. For increases (decreases) in the solar wind density F TP responds immediately by increasing (decreasing) from the steady state values. In both cases the response of F TP is transient, decaying to near initial steady state values even when the density change persists. The magnitude of the F TP response is proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 37 publications
4
20
1
Order By: Relevance
“…Since both the solar wind velocity and the IMF B z remain steady during the pressure pulse, it is the increase in density that causes both the Alfvénic Mach number and the solar wind Beta to increase. This data is in agreement with Ober et al (2007) who show that an increase in the solar wind density of this type (with other parameters held constant) can cause the open flux in the polar cap to increase. However, Boudouridis et al (2003Boudouridis et al ( , 2004Boudouridis et al ( , 2005 have demonstrated that, when a pressure pulse interacts with the magnetosphere, the auroral will tend to move poleward.…”
Section: Event 4: Active Bri (17 February 1998)supporting
confidence: 82%
See 4 more Smart Citations
“…Since both the solar wind velocity and the IMF B z remain steady during the pressure pulse, it is the increase in density that causes both the Alfvénic Mach number and the solar wind Beta to increase. This data is in agreement with Ober et al (2007) who show that an increase in the solar wind density of this type (with other parameters held constant) can cause the open flux in the polar cap to increase. However, Boudouridis et al (2003Boudouridis et al ( , 2004Boudouridis et al ( , 2005 have demonstrated that, when a pressure pulse interacts with the magnetosphere, the auroral will tend to move poleward.…”
Section: Event 4: Active Bri (17 February 1998)supporting
confidence: 82%
“…The IMF B z for all of the events is less than −5 nT. This differs from previous studies that state that steady magnetospheric convection usually occurs when 0 nT>B z ≥−5 nT (Sergeev et al, 1996;O'Brien et al, 2002;Tanskanen et al, 2005). Event 1 has a B z close to −6 nT and Event 2 starts with a B z of −5 nT before it starts to turn northward.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations